Fatigue, Cognitive Performance, and Subjective Recovery Time Estimation in High-Intensity Work. Issue 2 (2nd July 2016) - Ye, Taofeng; Pan, Xiao
Abstract : OCCUPATIONAL APPLICATIONS High-intensity work is associated with higher perceived fatigue, which could have a negative effect on both physical and cognitive performance. In particular, it may be unsafe and inefficient for workers to continue high-intensity physical work before complete recovery occurs (i.e., when heart rate returns to baseline levels). However, it is possible for workers to perform mental activities after subjective recovery time. After complete recovery, workers may return to performing the high-intensity physical work. The study evaluated a model of subjective recovery time using gender, relative body mass index, resting heart rate, perceived functional ability, and physical activity rating scores for high-intensity work tasks. With such subjective recovery time estimation, physical and mental work shift schedules that improve work efficiency can be designed. TECHNICAL ABSTRACT Background : Many research studies have investigated the relationship between high-intensity work and cognitive performance. High-intensity work induces higher perceived fatigue, which could have a negative effect on cognitive performance. Few studies have focused on cognitive performance changes during the recovery procedure, however, especially after subjective recovery time. Purpose : Subjective recovery time estimation was examined here, to provide a basis for determining schedules of work that require alternating physical and mental processing. Methods : A total of 47 participants performed reaction tasks aimed at measuring cognitive performance at four time points: before high-intensity work, after high-intensity work, after subjective recovery time, and after complete recovery time. Data from an estimation group ( n = 41) were used to derive the subjective recovery time estimate, while the remaining participant data ( n = 6) were used for validation. Results : Cognitive performance declined after high-intensity work but improved after subjective recovery time. Subsequent analysis indicated that subjective recovery time was significantly and positively correlated with gender, relative body mass index, and heart rate. Conversely, significant negative correlations were found between subjective recovery time and both perceived functional ability and physical activity rating. Gender, relative body mass index, heart rate, perceived functional ability, and physical activity rating score predicted subjective recovery time ( R 2 = 0.74). The results of the cross-validation analysis demonstrated that the predicted and actual subjective recovery times were similar. Conclusion : The established model is an efficient tool, using predictor variables that are feasible to obtain in naturalistic work environments, which could be used to estimate subjective recovery time. Along with an existing model that predicts complete recovery time, reasonable arrangements of work schedules that alternate mental and physical work could be designed to improve work efficiency and security.